2013
DOI: 10.2478/hukin-2013-0075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Finnish Sauna Session on White Blood Cell Profile and Cortisol Levels in Athletes and Non-Athletes

Abstract: The aim of the present study was to investigate the effect of Finnish sauna bathing on a white blood cell profile, cortisol levels and selected physiological indices in athletes and non-athletes. The study evaluated 9 trained middle-distance runners and 9 male non-athletes. The subjects from both groups participated in 15-minute sauna sessions until their core temperature rose by 1.2°C (mean temperature in the sauna room was 96° ± 2°C; relative humidity was 15 ± 3%) with a 2 minute cool down with water at a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 24 publications
3
42
0
4
Order By: Relevance
“…Furthermore, no research has been undertaken on the expression of HSPs and interleukins as a function of physical activity. Occasional reports on the effects of sauna on the bodies of athletes refer to changes in the number of leukocytes and the profile of the white blood cells [18]. In the opinion of the cited authors and the authors of the current study, adaptive changes to exercise should be reflected in differential induction of stress-related genes by sauna bathing.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, no research has been undertaken on the expression of HSPs and interleukins as a function of physical activity. Occasional reports on the effects of sauna on the bodies of athletes refer to changes in the number of leukocytes and the profile of the white blood cells [18]. In the opinion of the cited authors and the authors of the current study, adaptive changes to exercise should be reflected in differential induction of stress-related genes by sauna bathing.…”
Section: Introductionmentioning
confidence: 95%
“…For example, self-focused positive behaviors such as consuming dark chocolate, cocoa, or red wine have been shown to decrease markers of inflammation (Katz et al, 2011;Nicod et al, 2014). Favorable effects on inflammation and immune regulation have also been documented for napping (Faraut et al, 2015), having a sauna session (Pilch et al, 2013), and receiving regular massages (Rapaport et al, 2012). To distinguish the effects of producing positive behavior per se from the effects of its prosocial impact, this study contrasted the effects of positive behaviors directed at the self vs. others.…”
Section: Self-focused Behavior and Healthmentioning
confidence: 99%
“…Pilch et al (2008) contrastingly carried out a study in 10 females, and found that cortisol significantly increased after sauna. In addition, Pilch et al (2013) found significant increases in the cortisol values after sauna session they applied for 15 minutes to 9 trained middle-distance runners. Although there are not many studies examining the relationship between sauna and cortisol level in the literature, the results obtained in these limited studies seem to differ from one another.…”
Section: Sauna Hormonal Responsesmentioning
confidence: 95%